Research on the Practice and Innovation of the Smart Education Platform for "People's Stories" Ideological and Political Micro Courses in the Digital Background - Peng, Zhenzhen; Jiang, Liangrui; Liu, Shuyang (Transactions on Social Science, Education and Humanities Research, 2024)
With the gradual deepening of education digitalization in the field of education, smart education has become an important part of promoting Chinese path to modernization by piloting the reform and innovation of education informatization. In the new era, "people's character" has always been the most distinctive background of the Party and the country, and "people's stories" have a strong group bonding effect. Telling "people's stories" well is always the most important way to enhance the affinity and effectiveness of ideological and political education. Based on this, utilizing the digital characteristics of smart education, constructing a "People's Story" smart education platform for ideological and political micro courses that condenses empathy and consensus, softens conceptual conflicts, and integrates human care is a practical need to achieve intelligent extension and precise construction of ideological and political education.